Delayed freezing on the quality and shelf-life of Kalawa (Epinephelus spp.) - Perigreen, P.A., Joseph, A.C., Surendran, P.K. and (Fishery Technology, 2021)
Kalawa (Epinephelus spp.) caught on board FORV Sagar Sampada was frozen in the absolutely fresh condition as well as after keeping for 5 and 10h at ambient temperature. Evaluation of changes in the quality of these samples during storage at -20Â°C indicated appreciable difference between the fresh frozen and delayed frozen fish during the initial stages of storage. Fresh frozen and 5h delayed froze fish samples had a shelf-life of more than 62 weeks, whereas the 10h delayed frozen fish had a shelf-life of about 48 weeks.